2021
DOI: 10.3389/fimmu.2021.705511
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Validation of the Hypoxia-Related Signature of Evaluating Tumor Immune Microenvironment and Predicting Prognosis in Gastric Cancer

Abstract: BackgroundHypoxia is one driving factor of gastric cancer. It causes a series of immunosuppressive processes and malignant cell responses, leading to a poor prognosis. It is clinically important to identify the molecular markers related to hypoxia.MethodsWe screened the prognostic markers related to hypoxia in The Cancer Genome Atlas database, and a risk score model was developed based on these markers. The relationships between the risk score and tumor immune microenvironment were investigated. An independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 59 publications
(63 reference statements)
3
29
0
Order By: Relevance
“…The expression of ICAM1 was upregulated in rosacea and AD ( 73 , 74 ). SERPINE1 , a serpin peptidase inhibitor, is related to immune response in gastric cancer ( 75 ). PTGS2 , also known as COX-2, has a critical role in initiating inflammatory response and angiogenesis ( 76 , 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of ICAM1 was upregulated in rosacea and AD ( 73 , 74 ). SERPINE1 , a serpin peptidase inhibitor, is related to immune response in gastric cancer ( 75 ). PTGS2 , also known as COX-2, has a critical role in initiating inflammatory response and angiogenesis ( 76 , 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also identified that hypoxia could induce the high expression of immune checkpoint molecules, such as indoleamine 2,3-dioxygenase (IDO) and PD-L1 [ 50 , 51 ]. The expression of immune checkpoint molecules might be negatively associated with the infiltration of TILs and the prognosis in types of cancers [ 7 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, approximately 60% of dMMR patients may still progress and experience resistance to the same regimens [ 4 ]. Thus, many studies have focused on conducting comprehensive genome-wide analysis to identify the underlying molecular mechanisms of poor response to ICIs and distinct outcomes in other types of human malignancy [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the application of hypoxia gene signatures to reflect the degree of tumor hypoxia has taken the literature by storm with published signatures covering almost every solid tumor type (9,106). In addition to that, there has been an escalating number of papers focused not only on designating the hypoxic state of a tumor, but also interrogating the immune populations and immune activation status of that tumor depending on its hypoxic phenotype (189)(190)(191)(192)(193)(194)(195)(196)(197). The process generally entails first deriving a hypoxia signature in the cancer type of interest, which often takes the route of narrowing down a list of hypoxia-related differentially expressed genes (DEGs) between normal and tumor tissue, then determining which genes are correlated with patient prognosis, be it overall survival or disease-free survival.…”
Section: Unraveling the Hypoxia-immune Contexture In Silico: The Hits...mentioning
confidence: 99%